Propuesta de desarrollo turístico de la parroquia Fundochamba del cantón Quilanga - Abad Ojeda, Jonny Homero (2022)
Tourism is an activity that generates different impacts depending on the territories where we implement this activity; some of them with positive consequences, such as diversifying the economy of the local population, and others are negative and irreversible for the local population; and the quality of the environment. Therefore, tourism planning is paramount to ensure a correct dynamization of tourist destinations and territorial development based on sustainability criteria. The research work "PROPOSAL FOR TOURISM DEVELOPMENT IN THE FUNDOCHAMBA PARISH OF THE QUILANGA CANTON, PROVINCE OF LOJA", was designed to contribute to the development of tourism activity through the application of a participatory methodology with the authorities of the Fundochamba Parish, and actors involved in tourism activity and the community in general. The general objective of this research paper is to contribute to the development of tourism in Fundochamba Parish; based on the potential of its natural and cultural heritage. As well as its human component in the Parish of Fundochamba, in the canton of Quilanga, province of Loja. To achieve this goal, we developed three specific objectives; the first is to determine the tourism potential of Fundochamba Parish to exploit in its development. Moreover, the second is to know the perception of the community of Fundochamba regarding tourism in their Parish. Finally, the third objective is to establish strategies that would contribute to development tourism in the abovementioned Parish. To carry out this research, we applied methods such as the scientific method that allowed the verifying of information from sources. We conducted the analytical approach through which we analysis the environment of the attractions, the deductive method to corroborate that the reality conforms to the statement of the theoretical information. Moreover, to make a comparison with the information to be collected through direct observation, we used the descriptive method to analyze and synthesize the new data information. By employing this method, we described the current situation of the Parish. In addition to describing and making summary sheets of each attraction and cultural manifestations, it was also essential to use some research techniques such as the direct observation that allows the collection of all the information firsthand when making the inventory of natural attractions and cultural manifestations. Likewise, we obtained qualitative information from the Parish through the interview technique, which we applied to the actors directly involved in the tourism activity; and the MARPP methodology was also used, which enabled validating the information and prioritizing attractions and strategic objectives (See Annex 15, 16). 5 We verified the results obtained through the fulfillment of three specific objectives: the tourism diagnosis shows that there is a significant tourism potential in the Parish, with three natural attractions and six cultural attractions of hierarchy I and II, such as The Quiroz River, The Sauce Waterfalls, The Cuyes Hill, and among the cultural ones we have: the religious festival of Santa Marianita, the religious festival of the Divine Child, the religious festival of La Dolorosa, the religious festival of the Virgin of Fatima, and the parish festival, all of which require good planning to improve their hierarchy. In addition, we interview the president of the Parroquial GAD to find out his perception and attitude towards promoting tourism in his community. In the same way, we carried out surveys to find out the perceptions and attitudes towards tourism to the inhabitants of the Parish of Fundochamba. Finally, we have drawn up a SWOT matrix with internal and external advantage and disadvantage factors with fundamental guidelines that where considered to carry out or execute the strategies. The scope of the present research work is to contribute to the touristic development of the Parish through strategies that allow for good planning, management, and execution, resulting in quality standards of tourist products and services. Furthermore, in the environmental field, it will contribute to the care and protection of the natural attractions, raising awareness of responsible tourism to nature.